Hubungan antara kemampuan literasi digital dengan pencegahan berita hoaks di kalangan mahasiswa - Fachri Rizky Pratama; Neneng Komariah; Saleha Rodiah (Faculty of Communication, Padjadjaran University, 2022)
One of the impacts of the development of information and communication technology is the internet, which allows us to create and receive information from anywhere and at any time. This can have bad consequences because not all information on the internet can be accounted for. The purpose of this study is to determine how much the relationship between digital literacy skills consisting of internet searching skills, hypertextual navigation, content evaluation, and knowledge assembly with the prevention of hoax news in students of the Faculty of Communication Sciences, Padjadjaran University. The approach used in this research is a quantitative correlational approach. Data collection techniques were carried out by distributing questionnaires online and a literature study. Respondents in this study were active students of class 2017, 2018, and 2019 of the Faculty of Communication Sciences, Padjadjaran University, as many as 95 people. The sampling technique in this study used proportional stratified random sampling (random and stratified sampling). The results of this study show a significant relationship between students' digital literacy skills consisting of internet searching, hypertextual navigation, content evaluation, and knowledge assembly with the ability to prevent hoaxes in students of the Faculty of Communication Sciences, Padjadjaran University. This research is expected to add insight into the field of digital literacy and hoax prevention and can be a reference for further research, especially for those who will examine digital literacy at the Faculty of Communication Sciences, Universitas Padjadjaran.